A harmonic balance method for nonlinear fluid structure interaction problems. (May 2018) - Yao, W.; Marques, S.
Highlights: The article reports an improved time-integrator for the Harmonic-Balance approach. The solver exploits an approximate time integrator. The method is demonstrated for limit-cycle oscillations and vortex-induced vibrations. Abstract: Over the past decade the Harmonic-Balance technique has been established as a viable alternative to direct time integration methods to predict periodic aeroelastic instabilities. This article reports the progress made in using a frequency updating procedure, based on a coupled fluid-structural solver using the Harmonic-Balance formulation. In particular, this paper presents an efficient implicit time-integrator that accelerates the convergence of the structural equations of motion to the final solution. To demonstrate the proposed approached, the paper includes a detailed investigation of the impact of input parameters and exercises the method for two types of fluid-structural nonlinear instabilities: transonic limit-cycle oscillations and vortex-induced vibrations.